Augmented Reality Model Design in Urban Farming Learning Activity Simulation Based on GamePlay-Centric - Rossy, Virgiani Tulean; Rumagit, Paul (Journal of Multimedia Trend and Technology, 2025)
Based on available statistics, Indonesia ranks fourth globally in terms of the number of mobile phone users. Android is one of the operating systems (OS) for smartphones that is expanding quickly. Based on the results of the survey, Android-powered smartphones are the most popular. With 85.9% of smartphones running Android OS, the number of users in the first semester of 2023 grew very quickly. IOS, with 62.0% of users globally, came in second. This is a result of the growing selection of games and apps for smartphones running Android OS. Accompanied by the rapid development of Android smartphones, Augmented Reality (AR) has emerged. Augmented Reality is an environment that inserts 3D virtual objects into the real environment. Gameplay-centric in the context of games refers to a type of game where the main focus and highest priority is on game mechanics and player interaction with the game system itself. The core mechanics of the game are highly emphasized and carefully designed. This could be a deep combat system, challenging puzzles, responsive and satisfying controls, or interesting world exploration. Player enjoyment and engagement come from how players interact with the game. Challenges, feedback, and progress in the game are the main attractions. Other elements such as narrative (story), characters, and visuals may be present, but their roles are more supporting or secondary. They are not the main focus of the gaming experience. In fact, some gameplay-centric games may have minimal or no story at all.